Evaluation of confirmatory data following the Article 12 MRL review for aclonifen. (15th May 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: The applicant Bayer Crop Science submitted a request to the competent national authority in the Netherlands to evaluate the confirmatory data that were identified for aclonifen in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, an analytical method for enforcement in complex/no group matrices (spices) and additional four residue trials supporting SEU authorisation on peppers were submitted. The data gaps were considered satisfactorily addressed and the tentative MRLs can be confirmed in peppers, in seed and fruit spices and in flowers and leaves and herbs of herbal infusions. The previous consumer intake assessment remains valid.